Behavioral analysis of motor and non-motor impairment in rodent models of Parkinson's disease - Sheta, Razan; Bérard, Morgan; Musiol, Dylan; Martínez-Drudis, Laura; Oueslati, Abid (Frontiers in Aging Neuroscience, 2024)
Parkinson's disease (PD) is a prevalent neurodegenerative disorder characterized by the degeneration of dopamine neurons in the substantia nigra pars compacta, leading to motor and non-motor symptoms. While motor symptoms such as rigidity, tremor, bradykinesia/akinesia, and postural instability are well-recognized, non-motor symptoms including cognitive decline, depression, and anxiety also significantly impact patients' quality of life. Preclinical research utilizing animal models has been instrumental in understanding PD pathophysiology and exploring therapeutic interventions. Various approaches, including genetic manipulations and toxin-induced insults, aim to recapitulate both motor and non-motor aspects of PD in animal models. However, no single model fully replicates the complex spectrum of PD symptoms. Behavioral assessments play a crucial role in evaluating motor impairments in PD animal models, focusing on the manifestation of Parkinsonian motor phenotype. These assessments encompass locomotor activities, motor behavior abnormalities, and induced rotational behavior. Similarly, non-motor features are assessed through tests evaluating behavioral alterations such as depression, anxiety, and cognitive impairment. Although numerous animal models of PD have been developed, including non-human primates and both mammalian and non-mammalian species, this review focuses on motor and non-motor testing methodologies in rodent models, which are the most commonly used. Emphasizing genetic and toxin-induced PD models in mice and rats, we highlight key testing strategies and the significance of each method in addressing specific research questions and interpreting experimental data. By providing a comprehensive overview of these testing approaches, this review aims to advance understanding and foster progress in PD research.